(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the essence technology on level differentiations in the lichnostno -focused training to the mathematician. Besides, are stated a number of offers on realization of problems of education in the conditions of variability of formation, and also the lichnostno-focused training of pupils.